Careers in entrepreneurship - Smith, Tim; Vohra, Sweta; Silverman, Rachel; Docere Digital Studios (New Jersey : Films for the Humanities & Sciences, 2007)
Profiles entrepreneurs Paul Orfalea, founder of Kinkos, and Pleasant Rowland, creator of American Girl dolls. Orfalea and Rowland discuss how they turned their ideas into successful businesses
Executive producers, Tim Smith, Howard Stein
DVD format
Keywords: Orfalea, Paul; Rowland, Pleasant T; Entrepreneurship; Entrepreneurship -- Vocational guidance; Entrepreneurship -- Case studies; Success in business -- Case studies